Orbital metastasis of endocervical stromal sarcoma: a rare tumor and an uncommon metastasis - Seker, Mehmet Metin; Uslu, Ali Ugur; Ozer, Hatice; Seker, Ayse; Kacan, Turgut; Babacan, Nalan; Aker, Handan; Elagoz, Sahande (Menopause Review/Przegląd Menopauzalny, 2014)
Endocervical stromal sarcoma (ECSS) is a very rare uterine sarcoma. The most common presentation is pelvic mass and vaginal bleeding. The mainstay of treatment is surgery. There is no consensus on the adjuvant treatment. Relapses are usually in the pelvic and abdominal regions. To a lesser extent, lung, liver and bone metastases may be seen. A 46-year-old woman had total abdominal hysterectomy (TAH) with bilateral salpingo-oophorectomy (BSO) performed due to endometrial polyp and leiomyoma. Six months after the TAH-BSO, she was admitted to the hospital with cough and hemoptysis. A thoracic mass was detected, and a biopsy was done. The diagnosis was low-grade ECSS metastasis. One week after thoracotomy, she was admitted to the hospital with loss of vision in the left eye. An orbital mass was detected with magnetic resonance imaging. Endometrial and cervical pathology preparations were reassessed and were compatible with ECSS. We performed mammography, thorax, and abdomen and cranial imaging to rule out other malignancies that may cause lung and orbital metastasis. Partial remission was achieved with systemic chemotherapy and orbital radiotherapy. Orbital metastasis may be seen in ECSS patients. Although we have less knowledge about the choice of chemotherapeutic agents, ifosfamide and doxorubicin are effective in treating ECSS.